Black-box accuracy compensation for a cable-driven parallel robot - Schmidt, Valentin; Kraus, Wrer; Martin, Christoph; Jin, Xuejun; Pott, Andreas (2017 17th International Conference on Control, Automation and Systems (ICCAS), 2017)
This paper presents the findings of experiments done to increase the accuracy of a fully constrained cable-driven parallel robot with 8 cables and 6 degrees of freedom. Measurements were conducted using a Laser Tracker in 3 dof and the position accuracy mapped. Measurements were performed in a grid with 1920 points. From the measurement data distortion to the actual desired position is measured and using a linear approximation subsequent trajectories are compensated for any systematic errors. On an example robot, this black box correction brought an average improvement from 10.6 mm distance to the desired point to 2.47 mm distance from the desired point. This is a significant improvement m accuracy.